Playful interfaces to the archive and the embodied experience of data. Issue 2 (8th January 2020) - Hendery, Rachel; Burrell, Andrew
Abstract : Purpose: The purpose of this paper is to demonstrate the possibility for the galleries, libraries, archives and museums sector to employ playful, immersive discovery interfaces for their collections and raise awareness of some of the considerations that go into the decision to use such technology and the creation of the interfaces. Design/methodology/approach: This is a case study approach using the methodology of research through design. The paper introduces two examples of immersive interfaces to archival data created by the authors, using these as a springboard for discussing the different kinds of embodied experiences that users have with different kinds of immersion, for example, the exploration of the archive on a flat screen, a data "cave" or arena, or virtual reality. Findings: The role of such interfaces in communicating with the audience of an archive is considered, for example, in allowing users to detect structure in data, particularly in understanding the role of geographic or other spatial elements in a collection, and in shifting the locus of knowledge production from individual to community. It is argued that these different experiences draw on different metaphors in terms of users' prior experience with more well-known technologies, for example, "a performance" vs "a tool" vs "a background to a conversation". Originality/value: The two example interfaces discussed here are original creations by the authors of this paper. They are the first uses of mixed reality for interfacing with the archives in question. One is the first mixed reality interface to an audio archive. The discussion has implications for the future of interfaces to galleries, archives, libraries and museums more generally.